A multifaceted risk analysis of fathers' self‐reported physical violence toward their children. Issue 4 (23rd November 2016) - Ellonen, Noora; Peltonen, Kirsi; Pösö, Tarja; Janson, Staffan
Abstract : Existing research has shown that child maltreatment is carried out by both mothers and fathers. There is also an extensive body of literature analyzing reasons for mothers' violent behavior. Among fathers, reasons are less well studied, resulting in the lack of a comprehensive picture of paternal child abuse. In this study, 20 child‐, parent‐, and family‐related factors have been included in a combined analysis to assess which of these may pose a risk for fathers' severe violent behavior toward their children. The study is based on merged data from Finland and Sweden, in which an anonymous survey was answered by parents, based on representative samples of parents with 0–12‐year‐old children. The merged data set included 679 fathers and analyses were carried out using logistic regression models. Six percent of the fathers had committed severe violent acts, that is, slapped, hit, punched, kicked, bit, hit/tried to hit their child with an object or shook (under 2‐year‐old) their child at least once during the 12 months preceding the survey. Corporal punishment experienced by the fathers when they were children, or used by the father as a method of discipline, strongly increased the likelihood of severe violent acts. The findings emphasize the importance of preventing all forms of corporal punishment in seeking to minimize the occurrence of severe physical violence by fathers toward their children. Aggr. Behav. 43:317–328, 2017. © 2016 Wiley Periodicals, Inc.